Proficiency in Text Writing and Development of Workbook in Guided Writing - CASTILLO, DANDY (International Journal of Arts, Sciences and Education, 2025)
Writing proficiency is a crucial factor in a student’s academic success, yet it remains a challenge for many students in the Philippines. This study aims to determine the writing proficiency of Grade 8 students and to develop a workbook for guided writing in response to their needs. The researcher employed a descriptive-developmental design to examine students’ skills in various aspects of writing, including content, organization, grammar, and mechanics. Findings revealed that their writing proficiency was at a low level, indicating a need for further improvement, particularly in mechanics. The developed workbook was reviewed by experts and was proven to be an appropriate and effective instructional material. Results also showed that both teachers and students responded positively to the material. Based on the findings, the study recommends providing more writing exercises, remedial classes, utilization of the workbook, and implementation of various activities to enhance students’ writing skills. Furthermore, it is suggested that continuous training for teachers and in-depth research on the challenges students face in writing be conducted. This study offers a significant contribution to the improvement of writing proficiency and the advancement of education quality in the country.